TINJAUAN PENDEKATAN SISTEM DALAM MANAJEMEN KEUANGAN SEKOLAH ISLAM - Laksono, Arief; Sovia Mas Ayu; Yetri; Oki Dermawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic school financial management plays a crucial role in ensuring the achievement of educational goals through effective, transparent, and sharia-compliant resource management. This article aims to review the application of a systems approach to Islamic school financial management using a literature review. Data were obtained through analysis of various sources, such as books, scientific journals, research reports, and official documents related to Islamic educational financial management. The study results indicate that implementing a systems approach helps schools develop integrated financial planning, budgeting, implementation, monitoring, and evaluation, thereby increasing accountability and efficiency. However, the study also identified several challenges, such as limited human resources, suboptimal technology utilization, and low transparency in financial reporting. Therefore, strategies are needed to increase effectiveness through management digitization, human resource capacity building, and strengthening sharia-based governance. This article is expected to serve as a reference for Islamic educational institutions in developing more adaptive, professional, and sustainable financial management practices.